Analisis Putusan No. 88/Pdt.G/2021/PN Jember Tentang Kewajiban Tergugat Terhadap Perbuatan Melawan Hukum Pada Penggunaan Tanah Bersertifikat Ganda - Andhini Septiana; Ery Agus Priyono; Mira Novana Ardani; islamiyati islamiyati (Faculty of Law, Diponegoro University, 2023)
Land dispute cases often occur in the community, one of which is the issuance of double land certificates, namely a state where a piece of land has been registered into two or more certificates by BPN Jambi, one of which occurred in the case in decision No. 88 / Pdt.G / 2021 / PN Jember. The research was conducted to determine and analyze the defendant's liability for unlawful acts against the use of double-certified land. The research was conducted using normative and doctrinal juridical methods with descriptive analysis. The results showed that the issuance of multiple land certificates caused losses to overlapping rights to a land so that it became a loss of certainty of the rights and freedoms of one of the aggrieved parties to exercise control and to all control over the land that actually belonged to him. For such losses, then in accordance with Article 1365 of the Civil Code, ordered the defendant to return all double certificates to the Jambi City Land Agency and return the land owned by the plaintiff by legally purchasing the land owned by the plaintiff.